Analysis Of The Effect Of Cash Turnover and Receivable Turnover On Profitability Ratio In PT. Astra International, Tbk - Anggi Anggriani; M. Rimawan (Jurnal Ilmu Manajemen Profitability, 2022)
This study aims to identify and analyze the effect of cash turnover and accounts receivable turnover on profitability ratios at PT. Astra International, Tbk. This type of research is associative. The research instrument used is a list of tables containing data on net sales, average cash, average receivables, net income after tax, and total assets at PT. Astra Internasional, Tbk for 10 years, from 2011 to 2020. The population used in this study is the entire financial report of PT. Astra Internasional, Tbk for 30 years since being listed on the IDX for 30 years, namely from 1990 to 2020. The sample in this study is the financial statements of PT. Astra Internasional, Tbk for 10 years, namely from 2011 to 2020. The sampling technique used in this study is a purposive sampling technique, with the criteria (1) financial statement data is available for 10 consecutive years, namely 2011-2020 (2 ) 10-year sample data already represents existing population data for research needs. Data collection techniques used are documentation and literature study. The data analysis technique used is component analysis, classical assumption test, multiple linear regression analysis, multiple correlation coefficient, determination test, t test and f test. The results showed that cash turnover and accounts receivable turnover together had a significant effect on profitability at PT. Astra International, Tbk.